2018
DOI: 10.7150/thno.27806
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of OGT promotes cisplatin resistance by inducing autophagy in ovarian cancer

Abstract: Cisplatin resistance significantly affects the survival rate of patients with ovarian cancer. However, the main mechanism underlying cisplatin resistance in ovarian cancer remains unclear.Methods: Immunohistochemistry was used to determine the expression of OGT, OGA and O-GlcNAc in chemoresistant and chemosensitive ovarian cancer tissues. Functional analyses (in vitro and in vivo) were performed to confirm the role of OGT in cisplatin resistance. Autophagy-related proteins were tested by western blot. Transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 46 publications
2
86
0
Order By: Relevance
“…Briefly, autophagy is a highly conserved cellular process during evolution, which is induced by diverse pathologies and cellular stresses containing nutrient deprivation, endoplasmic reticulum stress, and hypoxia 17 . Autophagy has also been involved in cancer resistance to multiple chemotherapeutic drugs, including cisplatin 18 , paclitaxel 19 , and gemcitabine 20 . Autophagy plays a vital role in regulating colorectal cancer chemoresistance, blocking of which will be developed as a promising therapy strategy for colorectal cancer treatment 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, autophagy is a highly conserved cellular process during evolution, which is induced by diverse pathologies and cellular stresses containing nutrient deprivation, endoplasmic reticulum stress, and hypoxia 17 . Autophagy has also been involved in cancer resistance to multiple chemotherapeutic drugs, including cisplatin 18 , paclitaxel 19 , and gemcitabine 20 . Autophagy plays a vital role in regulating colorectal cancer chemoresistance, blocking of which will be developed as a promising therapy strategy for colorectal cancer treatment 21 .…”
Section: Introductionmentioning
confidence: 99%
“…PBK promotes the metastasis of serous ovarian carcinoma and confers cisplatin resistance [17]. OGT was downregulated in ovarian cancer, which in turn, promotes cisplatin resistance by inducing autophagy [18]. The previous studies found that MARCH5 and PKP3 regulated the autophagy and invasion of ovarian cancer [7, 19].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the role of OGT in the liver revealed that phosphorylated OGT can promote O-GlcNAc modification and activate Ulk proteins by potentiating AMPK-dependent phosphorylation, and that ablation of OGT could reduce autophagic flux [16]. In ovarian cancer cells downregulation of OGT induces cell autophagy through O-GlcNAc modification of SNAP-29, which contributes to cisplatin resistance [22]. OGT has also been found to regulate bladder cancer cell autophagy.…”
Section: Validationmentioning
confidence: 99%